Prevalence of osteoporosis and osteoporotic fractures in postmenopausal women with type 2 diabetes mellitus - Lamia Oulkadi; Bouchra Amine; Imane El binoune; Samira Rostom; Rachid Bahiri (Verduci Editore, 2021)
Type 2 diabetes mellitus (T2DM) and osteoporosis are chronic diseases with increasing prevalence. The aim of this study was to determine the prevalence of osteoporosis and osteoporotic fracture in women with T2DM and to identify predictive factors of fracture occurrence. The prevalence of osteoporosis and fractures in postmenopausal women with T2DM was 23.1% and 16.9%, respectively. 46.2% of T2DM patients had normal bone mineral density (BMD) (P<0.01) and 58.5% of control subjects had osteopenia (P<0.01). Incidence of fracture in T2DM patients with osteopenia was significantly increased versus control subjects when stratified according the BMD (P=0.009). By stratifying T2DM patients according to fractures, factors that were significantly associated with occurrence included T2DM duration (P=0.038), use of insulin (P=0.017), and lower BMD (P=0.048). Our study suggests that there was a higher prevalence of fracture in T2DM patients compared to control subjects and a significant difference in BMD was found between the groups. We also showed that insulin use, low BMD, and long duration of T2DM are factors associated with an increased risk of bone fracture.